Analisis Dinamika Kepribadian Id, Ego, Superego Pada Tokoh Utama Cerita Pendek “rupanya aku bisa” Karya maria klavia.a - Very Angga Saputra; Muhammad Fatikhul Ikhwan; Eva Dwi Kurniawan (JOURNAL SAINS STUDENT RESEARCH, 2024)
The aim of this research is that the researcher wants to analyze more deeply the dynamics of the Id, Ego, Superego personality of the main character in the short story entitled "Apparently I Can" by Maria Klavia.A using qualitative descriptive research methods and a literary psychology approach using psychoanalytic theory from Sigmund Freud, the formulation of the problem of this research is, what is the personality structure of the main character named Adit in the short story entitled "Apparently I can" by Maria Klavia. A. The results of this research show that the personality structure of Adit's character Id is manifested by expressing his discomfort with unpleasant stimuli occurring around him, while Adit's ego is represented through his lack of self-confidence because he considers that his abilities are not comparable to his abilities. by other people. Then the superego of Adit's character is shown through a scene that depicts Adit's concern for his friend. This concern is manifested in the form of his behavior in offering food to his friend because he knows that his friend has not eaten before.